Everything, Everything - Reguera, Ana de la; 1977-; 1972-; Yoon, Nicola; Rose, Anika Noni; Robinson, Nick; 1995; Goodloe, J. Mills; Morgenstein, Leslie; Meghie, Stella; Stenberg, Amandla; Dutton, Elysa; et al. (Burbank, CA, 2017)
It tells the unlikely love story of Maddy, a smart, curious and imaginative eighteen-year-old who due to an illness cannot leave the protection of the hermetically sealed environment within her house, and Olly, the boy next door who wont let that stop them. Maddy is desperate to experience the much more stimulating outside world, and the promise of her first romance.
Keywords: Friendship; Drama; Drama; Drama; DVDs; Young adults; Parent and teenager; Severe combined immunodeficiency; Drama; First loves; Drama; Mothers and daughters; Drama; Feature films; Romance films; Video recordings for the hearing impaired; Fiction films; Video recordings for people with visual disabilities; Film adaptations; Drama; Video recordings for the hearing impaired; Video recordings for people with visual disabilities; Drama; Feature films; Romantic plays; Fiction films; Film adaptations; Romance films